2021
DOI: 10.3171/2019.11.jns192457
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after endoscopic endonasal surgery for nonfunctioning pituitary macroadenomas

Abstract: OBJECTIVENonfunctioning pituitary adenomas are benign, slow-growing tumors. After gross-total resection (GTR) or subtotal resection (STR), tumors can recur or progress and may ultimately require additional intervention. A greater understanding of long-term recurrence and progression rates following complete or partial resection and the need for further intervention will help clinicians provide meaningful counsel for their patients and assist data-driven decision-makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
6
21
3
Order By: Relevance
“…Furthermore, an overall beneficial effect on pituitary hormone secretion was found. The maximum numbers of post-surgery new insufficiencies per axis was 10% which is in accordance with previous papers reporting data on deterioration of pituitary function 20,21,24,27 . Analogous to other studies we identified tumour size as a predictor of post-surgery insufficiency for the 3 investigated pituitary axis 6,26,27 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, an overall beneficial effect on pituitary hormone secretion was found. The maximum numbers of post-surgery new insufficiencies per axis was 10% which is in accordance with previous papers reporting data on deterioration of pituitary function 20,21,24,27 . Analogous to other studies we identified tumour size as a predictor of post-surgery insufficiency for the 3 investigated pituitary axis 6,26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…al. 20 also found an increased risk at developing anterior pituitary dysfunction after reoperations (n=19), however it was not specific for the adrenal axis as seen in the present study. By contrast, Chang et.…”
Section: Discussioncontrasting
confidence: 82%
“…A high Ki-67 index requires neurosurgeons to obtain gross-total resection and prepare for higher probability of compression and tissue adhesion in the surrounding structures (6). Furthermore, a high Ki-67 index may prompt a closer follow-up or early radiation therapy (7). Ugga et al proposed a machine learning model based on T2W magnetic resonance imaging (MRI) for the prediction of the Ki-67 proliferation index class (8).…”
Section: Introductionmentioning
confidence: 99%
“…Another factor to take into account, although it is outside the objective of this study, would be tumour hardness [33]. On the other hand, we observed that GTR protects against postoperative hormonal worsening, and it is known that there are higher GTR rates when the tumour volume is lower [22] [34], as demonstrated in our study. We would say that patients in whom pituitary gland is visualized on preoperative MRI, with smaller tumour size and in which GTR is achieved, are the ones more likely of having at least hormonal stability after surgery with a smaller number of axes affected.…”
Section: Discussionmentioning
confidence: 49%